Visualizing the Other: Media Representations of Nina Khrushcheva During the Khrushchevs' State Visit to the United States in 1959 - Doğan, Mariya (Review of International American Studies, 2024)
The gender discourse had an important role in the ideological confrontation between the United States and the Soviet Union and proved to be an effective weapon of the Cold War. In American imagination, the image of a Soviet woman became an epitome of ‘the other’ which both personified the threat of communism and eased domestic anxieties about rigid gender roles in the post-war US. However, the Cold War was not a homogeneous process. The period from the mid-1950s to the early 1960s referred to as the Khrushchev Thaw, was characterized by attempts of peaceful coexistence between the two superpowers culminating in Khrushchev’s visit to the United States in September 1959. Nina P. Khrushcheva, the wife of the first secretary of the Communist Party, became the first high-rank communist woman to tour the United States with an official visit. The American press took this opportunity to humanize the image of a woman from the other side of the iron curtain and, consequently, defuse tensions on the international stage. Khrushcheva’s visit became a turning point in constructing the image of Soviet femininity, introducing a stereotype of different but not intimidating womanhood. Despite the fact that the fragile hopes for peace between the Western and Eastern Blocs were shattered soon after Khrushchev’s visit, the popular rhetoric of the Soviet femininity was transformed. The present article analyzes the shift in the Soviet gender codes presented in the American newspapers, and puts them into historical context to show how international policies can gain human face in the press.